Effect of weight restriction strategies in judokas - Gordon, Y.; Souglis, A.; Andronikos, G. (Journal of Physical Education and Sport, 2021)
Objective/Background: Prior to and surrounding a Judo competition athletes manipulate Body Mass (BM) to gain a theoretical advantage when competing against a weaker opponent using a universally practiced tactic known as rapid weight loss (RWL). RWL is commonly used however there is scarcity of research examining its physiological effects which may include muscle damage and increased risk of injury among others. In addition, psychological effects related to body image, eating behaviours, and emotional responses were found to be attributed to weight restrictions strategies in Judo. The current study aimed to identify the methods used to lose weight, the reasoning behind doing so and the potential effects of those strategies. The physiological and psychological effects related to mental well-being and mood among elite judokas were investigated. Materials and Methods: 12 elite Judo athletes volunteered for this investigation (n = 12, 7 females, 5 males; aged = 20 - 28 years). Qualitative data was gathered with semi structured interviews and was analysed through inductive thematic analysis. Results: Key themes identified were that participants were intrinsically motivated to compete, partake in dehydration, starvation, and hot baths as the main methods of RWL. This negatively affected mood and mental wellbeing causing maladaptive eating behaviours and BM issues. Conclusions: It was evident that a variety of extreme methods used for RWL can have an adverse effect on athletes both physically and psychologically. However, this can be mainly attributed to the lack of knowledge concerning safe weight loss strategies since athletes were receiving guidance and advice from coaches and teammates instead of health professionals.